Effects of Plant Growth Promoting Rhizobacteria on Seed Germination Characteristics of Tomato and Lettuce - Mangmang, Jonathan; Deaker, Rosalind; Rogers, Gordon (Department of Agronomy and Horticulture, IPB University, 2014)
Plant growth promoting rhizobacteria (PGPR) represent a wide genera of rhizospheric bacteria which, when introduced in association with the host plant in proper amount, can enhance plant growth and productivity. A series of experiments were conducted to determine the germination responses of tomato and lettuce to PGPR inoculation. Seeds were inoculated with different strains of Azospirillum brasilense Sp7, Sp7-S and Sp245, Herbaspirillum seropedicea and Burkholderia phytofirmans PsJNT. The results reveal that Sp7-S inoculation yielded better germination rate and total germination of tomato. PGPR inoculation, except Sp7, produced longer (28%) and heavier (37%) roots with superior vigor. In lettuce, PGPR strains, except B. phytofirmans PsJNT, and Sp7 and B. phytofirmans PsJNT, enhanced germination vigor and length of roots (26%), respectively. The results provide further evidence concerning their importance as PGPR and indicate the potential of exploiting some of these PGPR to improve seedling emergence and establishment of vegetables.